The Freshwater Naiads of the Lower End of the Wabash River, Mt. Carmel, Illinois to the South - Clarence F. Clark (Hello World!, 1976)
The freshwater naiads of the Wabash River have been studied intermittently for over 100 years by both conchologists and commercial shell collectors. Dating from the 1820's, the papers of Thomas Say, of New Harmony, Indiana, are among the first published on the American freshwater Mollusca. Call (1900) referred to Say as the father of American conchology. The extensive work of Say facilitated the description of many new species of freshwater naiads, updated distribution data for others, and established the Mollusca of the Wabash River among the best known in the United States.